Faktor-Faktor Yang Mempengaruhi Penerimaan Pajak - irfan irfan (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The purpose of this study was to determine the effect of taxpayer awareness, tax services, and knowledge of taxpayers on tax revenues at KPP Pratama Deli Serdang. To avoid misunderstandings in understanding the discussion in this study, the authors limit the research problem to individual taxpayers at KPP Deli Serdang. This study uses an associative research design. The sample in this study were individual taxpayers who reported their Annual Tax Return in March 2017. Due to limited time and research locations outside the city, in this study the number of research samples was only 50 people, this study used multiple linear analysis techniques using SPSS version 19 is the t-test and f-test methods, while the results of the research are that there is an influence between taxpayer awareness on tax revenues at KKP Pratama Deli Serdang, there is a significant effect between tax services on tax revenues at KPP Pratama Deli Serdang, there is an effect on mandatory knowledge tax on tax revenues at KPP Pratama Deli Serdang.